1990
DOI: 10.1111/j.1365-2559.1990.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Small cell neuroendocrine carcinoma of the rectum associated with chronic ulcerative colitis

Abstract: ReferencesAslani M, Ahn G, Scully RE. Serous papillary cystadenoma of borderline malignancy of broad ligament. Int. 1. Gynecol. Pathol. Chandraratnam E, Leong AS-Y. Papillary serous cystadenoma of borderline malignancy arising in a parovarian paramesonephric cyst. Light microscopic and ultrastructural observations. Histopatho-DAblaing In G . Klatt EC. Dirocco G . Hibbard LT. Broad ligament serous tumour of low malignant potential. Int. 1. Gynecol. Pathol. 1983: 2(1); 93-99. Duvall E, Survis JA. Borderline turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…[3][4][5][6][7] Poorly differentiated neuroendocrine carcinomas (NECs) are only anecdotally reported in association with Crohn's disease 7 and in ulcerative colitis (UC). [7][8][9][10][11][12][13][14][15][16][17][18] In this article, we report the case of a patient affected by UC who developed an NEC G3 of the sigmoid colon, and we review the clinicopathological features of the cases reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Poorly differentiated neuroendocrine carcinomas (NECs) are only anecdotally reported in association with Crohn's disease 7 and in ulcerative colitis (UC). [7][8][9][10][11][12][13][14][15][16][17][18] In this article, we report the case of a patient affected by UC who developed an NEC G3 of the sigmoid colon, and we review the clinicopathological features of the cases reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Ils sont plus fréquents dans le sexe masculin avec un âge moyen de diagnostic de 50 ans [12] (notre patiente était âgée de 45 ans). Aucun facteur de risque n'est établi, cependant trois cas de carcinomes indifférenciés à petites cellules anorectaux ont été rapportés chez des hommes homosexuels et VIH positifs [10,13] et deux cas associés à une colite ulcérée [5,14].…”
Section: Discussionunclassified
“…Elles sont caractérisées par la présence de granules neurosécrétoires exprimant différents peptides, et c'est l'immunohistochimie qui les met en évidence. Pour le canal anal, c'est essentiellement le NSE, le Leu-7 (CD57), la chromogranine A (CGA), la synaptophysine (notre cas) et la sérotonine qui sont les plus retrouvés [6,10,11,14,[18][19][20][21][22]. Actuellement, le diagnostic de carcinomes à petites cellules est posé grâce à l'association de deux éléments, l'aspect histomorphologique et au moins deux réactions immunohistochimiques positives.…”
Section: Discussionunclassified
“…Interestingly, in a report from Taiwan, there were 2 patients with small cell carcinomas that were believed to represent gastrointestinal metastases from a primary pulmonary site, possibly emphasizing the difficulty in defining their origin in some cases [6] . Scattered reports are available on poorly differentiated neuroendocrine carcinoma with inflammatory bowel disease have been notedwith an equally dismal outcome [7][8][9] . In a recent report by Grassia et al [1] , however, surveillance studies were completed during the preceding year, and yet, large lesions in the most distal colon were eventually detected later.…”
Section: To the Editormentioning
confidence: 99%